1976
DOI: 10.1002/hlca.19760590438
|View full text |Cite
|
Sign up to set email alerts
|

Addition du chlorure de nitrosyle et de l'oxyde d'azote(III) sur l'allyltriméthylsilane et sur l'allylbenzyldiméthylsilane

Abstract: Le sens de l'addition du chlorure de nitrosyle sur ces composCs organosiliciCs se ddduit de l'effet inductif rdpulsif du groupement trialkylsilyle [6] [7] et de la stabilitd plus grande du carbocation secondaire (rbgle de Markowaikoff). On peut donc attribuer au nitrosochlorure la formule (R1R2R3) Si-CHz-CHCl-CH2NO.La structure des pseudonitrosites obtenus peut Ctre dCrivCe de deux manihes selon que I'on considkre un rri6canisme ionique ou un mCcanisme radicalaire. Si nous appliquons le m6canisme ionique propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Many methods can be used to convert olefins or nitroalkanes to nitro olefins. Nevertheless, we found that none of those was applicable to synthesis of 1-nitro-3-(triisopropylsilyl)-1-propene with success, except the procedure developed by Jolibois et al Scheme shows our results, in which allyltriisopropylsilane was allowed to react with nitrosyl chloride in chloroform at −60 °C. We then oxidized the resultant nitroso dimer intermediate with m -chloroperbenzoic acid ( m -CPBA) to give the corresponding nitro compound.…”
Section: Introductionmentioning
confidence: 81%
“…Many methods can be used to convert olefins or nitroalkanes to nitro olefins. Nevertheless, we found that none of those was applicable to synthesis of 1-nitro-3-(triisopropylsilyl)-1-propene with success, except the procedure developed by Jolibois et al Scheme shows our results, in which allyltriisopropylsilane was allowed to react with nitrosyl chloride in chloroform at −60 °C. We then oxidized the resultant nitroso dimer intermediate with m -chloroperbenzoic acid ( m -CPBA) to give the corresponding nitro compound.…”
Section: Introductionmentioning
confidence: 81%
“…68), the product of radical addition (49) was obtained, whereas neither oxime (48) nor nitrosonitrites was formed. The additions to 2,5-dimethoxypropenylbenzene (50), [153] cinnamyl acetate (86), [154] allyltrimethylsilane (51), [155] and many other alkenes [149] exhibits the selectivity of radical mechanism. [156] Generally, a polar reaction (e. g. Eq.…”
Section: C-nitrosationmentioning
confidence: 99%